2005
DOI: 10.1108/00022660510628480
|View full text |Cite
|
Sign up to set email alerts
|

Free vibration analysis of delaminated composite pretwisted shells

Abstract: PurposeTo investigate the effects of delamination on free vibration characteristics of graphite‐epoxy composite pretwisted cylindrical shallow shells of various stacking sequences considering length of delamination as a parameter.Design/methodology/approachA multipoint constraint algorithm which leads to unsymmetric elastic stiffness matrix is incorporated into an eight noded isoparametric plate bending finite element to satisfy the compatibility of deformation and equilibrium of resultant forces and moments a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2009
2009
2016
2016

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 14 publications
0
13
0
Order By: Relevance
“…The numerical results obtained are compared and validated with the results of [Liew et al 1994;Krawczuk et al 1997;Karmakar et al 2005] as furnished in Table 1, Figure 3, and Table 2, respectively. The comparative study shows excellent agreement with the previously published results and hence demonstrates the capability of the code developed and proves the accuracy of the analyses.…”
Section: Validation Of Resultsmentioning
confidence: 90%
See 1 more Smart Citation
“…The numerical results obtained are compared and validated with the results of [Liew et al 1994;Krawczuk et al 1997;Karmakar et al 2005] as furnished in Table 1, Figure 3, and Table 2, respectively. The comparative study shows excellent agreement with the previously published results and hence demonstrates the capability of the code developed and proves the accuracy of the analyses.…”
Section: Validation Of Resultsmentioning
confidence: 90%
“…Three delaminations Present FEM [Karmakar et al 2005] Present FEM [Karmakar et al 2005] Table 2. shells under single, double, triple, and quadruple delaminations with different twist angles, as furnished in Table 3.…”
Section: Two Delaminationsmentioning
confidence: 99%
“…This equation can be considered as a special case for element 1 and Z 1 equal Figure 3. Influence of the relative position of delamination on the first natural frequency of the composite cantilever beam [Krawczuk et al 1997].…”
Section: Multipoint Constraintmentioning
confidence: 99%
“…[2] studied the effect of delamination on the natural frequencies of a laminated composite beam, results showed that an increase in delamination length increases the reduction in the natural frequency. [3] presented the effect length of delamination on the free vibration of composite pre-twisted shells with different stacking sequences. A finite element model has been presented by [4] to analyse the natural frequencies of delaminated composite beams.…”
Section: I I Introduction Ntroduction Ntroduction Ntroductionmentioning
confidence: 99%